2003
DOI: 10.1002/jsfa.1392
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative bioactive compounds assessment and their relative contribution to the antioxidant capacity of commercial orange juices

Abstract: Dietary recommendations for healthy eating include the consumption of fruit juices whose health effects are ascribed, in part, to carotenoids, phenolic compounds and vitamin C. These bioactive compounds have been implicated in the reduction of degenerative human diseases, mainly due to their antioxidant potential. Orange juice is characterized by substantial accumulation (apart from ascorbic acid) of flavonoids and carotenoids. Commercial orange juice is the main human dietary source of antioxidant compounds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
124
1
13

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(156 citation statements)
references
References 31 publications
18
124
1
13
Order By: Relevance
“…Thermal treatment did not have an effect on apple juice titratable acidity, in agreement with other authors [39], while in orange juice significant differences were observed between freshly squeezed and commercial (pasteurised and frozen without previous pasteurisation) juices analysed in the middle of their commercial shelf life [40].…”
Section: +4supporting
confidence: 91%
“…Thermal treatment did not have an effect on apple juice titratable acidity, in agreement with other authors [39], while in orange juice significant differences were observed between freshly squeezed and commercial (pasteurised and frozen without previous pasteurisation) juices analysed in the middle of their commercial shelf life [40].…”
Section: +4supporting
confidence: 91%
“…155 2.4.3. Antioxidant activity Antioxidant activity was assessed using the free radical scavenging activity of the samples evaluated with the stable radical 2,2-Diphenyl-1-picrylhydrazyl (DPPH), according to the method described by Sánchez-Moreno et al (2003). 10 g of seedless 160…”
Section: Grape Characterizationmentioning
confidence: 99%
“…Studies have shown that high consumption of fruits and vegetables can provide health benefits due to their antioxidant components including carotenoids, phenolic, flavonoids compounds and vitamins (Sánchez-Moreno et al, 2003). Watermelon (Citrullus lanatus) is a native plant of tropical Africa; it has relatively low vitamin C content compared with other citrus fruits.…”
Section: Introductionmentioning
confidence: 99%